Cerebro‐renal interaction and stroke. (17th October 2020) - Shah, Birva; Jagtap, Priya; Sarmah, Deepaneeta; Datta, Aishika; Raut, Swapnil; Sarkar, Ankan; Bohra, Mariya; Singh, Upasna; Baidya, Falguni; Kalia, Kiran; Borah, Anupom; Dave, Kunjan R.; et al.
Abstract: Stroke is an event causing a disturbance in cerebral function leading to death and disability worldwide. Both acute kidney injury and chronic kidney disease (CKD) are associated with an increased risk of stroke and cerebrovascular events. The underlying mechanistic approach between impaired renal function and stroke is limitedly explored and has attracted researchers to learn more for developing therapeutic intervention. Common risk factors such as hypertension, hyperphosphatemia, atrial fibrillation, arteriosclerosis, hyperhomocysteinemia, blood‐brain barrier disruption, inflammation, etc. are observed in the general population, but are high in renal failure patients. Also, risk factors like bone mineral metabolism, uremic toxins, and anemia, along with the process of dialysis in CKD patients, eventually increases the risk of stroke. Therefore, early detection of risks associated with stroke in CKD is imperative, which may decrease the mortality associated with it. This review highlights mechanisms by which kidney dysfunction can lead to cerebrovascular events and increase the risk of stroke in renal impairment. Abstract : Figure representing the various steps that lead towards stroke following kidney dysfunction.